Mechanistic modeling of continuous capture step purification of biosimilar monoclonal antibody therapeutic - Deulgaonkar, Prashant; Bhambure, Rahul; Prasad, Bhaskarjyoti; Mishra, Ashok; Tiwari, Sanjay; Mody, Rustom (Journal of Chemical Technology and Biotechnology, 2022)
{BACKGROUND Continuous multicolumn Protein A chromatography offers various advantages for capture stage purification of monoclonal antibody therapeutics, like higher productivity and resin capacity utilization, lower buffer consumption, small footprint, etc. Due to the complexity of the continuous process, experimental optimization is time-consuming and cost-intensive. This investigation proposes a hybrid process development approach integrating experimental and mechanistic modeling for time- and cost-effective development and optimization of continuous Protein A affinity chromatography. RESULTS Productivity and capacity utilization of the continuous CaptureSMB process under varying operating conditions were predicted using the Chromatography Analysis and Design Toolkit (CADET) framework and validated with experimental results. Effects of critical process parameters like feed concentration (c(0)), loading breakthrough (s) and residence time (RT) on productivity and capacity utilization were evaluated. Model predictions were validated using the experimental results proving the reliability and feasibility of the modeling approach. At 15.00 +/- 0.20 mg mL(-1) feed model mAb concentration, the model-based approach predicted the best performance giving 27.56 g L-1 h(-1) productivity (RT = 2 min
Keywords: CaptureSMB; continuous chromatography; Mathematical modeling; Protein A; simulation

Mapping time dependent disulfide bond formation during in-vitro refolding of recombinant peptibody: a Fc-fusion protein - Kumthekar, Rupali; Rana, Sunil; Ughade, Santosh; Bhambure, Rahul (Biochemical Engineering Journal, 2023)
Disulfide bonds are commonly found in covalent interactions, which play a vital role in establishing the three-dimensional structure of proteins and maintaining their biological activity. This investigation is focused on time dependant mapping of intra and inter-disulfide bonds during in-vitro refolding of recombinant peptibody using LC-ESI-MS/MS. The selected recombinant peptibody is a homodimeric, aglycosylated Fc-fusion protein expressed in E. coli. The amino acid sequence in the disulfide bond containing peptides was confirmed at MS/MS level using the CID-based fragmentation approach. During in-vitro refolding of peptibody, a peptide with inter -chain disulfide bond is observed post 4 h, with low area intensity, and it reached a maximum in 96 h. How-ever, maximum area intensity was reached for the intra-chain disulfide bond in 72 h. Since cysteine residues responsible for intra-chain disulfide bonds are present in complex part of the Fc domain, formation of intra-chain disulfide bonds may be an overall rate-limiting step in recombinant Romiplostim refolding. Proper folding and contributions by non-covalent interactions will be required to form intra-chain disulfide bond. Monitoring time -based formation of such non-covalent interactions was carried out using intrinsic fluorescence during protein refolding. Observations from intrinsic fluorescence show that 4-6 h is most crucial time for domain formation. Observations from this study will help characterize structural integrity and quality during process and product development for consistent product quality.
Keywords: Disulfide bond formation; In -vitro refolding; Intrinsic fluorescence; Mass spectroscopy; Peptibody; Time based mapping

Mechanistic modeling of size exclusion chromatography-assisted in vitro refolding of the recombinant biosimilar teriparatide (PTH-34) - Ughade, Santosh; Rana, Sunil; Nadeem, Mohd; Kumthekar, Rupali; Mahajani, Sanjay; Bhambure, Rahul (ACS Omega, 2024)
In vitro protein refolding is one of the critical unit operations in manufacturing recombinant peptides expressed using Escherichia coli as host cells. This study is focused on designing size exclusion chromatography-assisted in vitro refolding process for biosimilar recombinant parathyroid hormone. Inclusion bodies (IBs) of recombinant parathyroid hormone were solubilized at higher pH, and in vitro refolding was performed using size exclusion chromatography. In the first part of the investigation, DoE-based empirical optimization was performed to achieve a higher refolding yield for a biosimilar recombinant parathyroid hormone. The effect of solubilized inclusion body (IB) feed volume, concentration of IBs, and residence time on in vitro refolding of recombinant teriparatide was studied using the Box-Behnken design. Size exclusion chromatography (SEC)-assisted in vitro refolding was performed at 8 C-degrees at pH 10.5 by using 20 mM Tris buffer. The maximum refolding yield of 98.12% was achieved at feed volume (12.5% of CV) and 20 mg/mL inclusion body (IB) concentration with a residence time of 50 min and a purity of 66.1% based on densitometric analysis using SDS-PAGE. In the latter part of the investigation, the general rate mechanistic model framework for size exclusion chromatography was developed and validated with the experimental results. The developed model helped in the accurate prediction of the elution volumes and product yield. The developed model also helps to predict the elution performance of a scalable column a priori. Post in vitro refolding, the formation of the native peptide structure was examined using various orthogonal analytical tools to study the protein's primary, secondary, and tertiary structures. The developed hybrid process development approach is a valuable tool toachieve high-yield, scalable refolding conditions for recombinant proteins without disulfide bonds.